Rapid/point-of-care syphilis testing in high-income countries: insights and implementation challenges from the authors’ experience in Canada - Ameeta E. Singh; Byron M. Berenger; Kevin Fonseca (Journal of Clinical Microbiology, 2026)
ABSTRACT Rapid/point-of-care tests (RPOCTs) for syphilis can significantly contribute to addressing the ongoing syphilis epidemic in high-income countries (HICs) for individuals facing barriers to traditional healthcare access and who may be less likely to return for follow-up appointments. By providing immediate diagnosis and treatment, RPOCT helps reduce disease progression and transmission to sex partners and from pregnant women to their fetus. This review offers an overview of the resurgence of syphilis in HICs and discusses the advantages and limitations of existing RPOCTs. We also share our experience with implementing RPOCT programs and emphasize the importance of successful implementation, which requires a strategic approach that considers RPOCT performance characteristics, local epidemiology, and the specific needs of each setting. Community members and site leaders should be involved in program planning and implementation to ensure they are rooted in the lived experiences and knowledge of those most impacted. Equally important is engaging policymakers, public health authorities, and laboratories to support program adoption and sustainability. Patient, healthcare provider, and laboratory acceptance of RPOCT is crucial when selecting test kits and planning program delivery. Ongoing monitoring and evaluation are essential to assess program effectiveness and allow for strategic adjustments based on feedback and outcomes. This continuous improvement process optimizes the impact of RPOCT initiatives and maximizes public health efforts. Further research is needed to explore existing and new technologies that can enhance the accuracy of diagnosing syphilis infections and cost-effectiveness studies to support their use.